2013
DOI: 10.20452/pamw.1821
|View full text |Cite
|
Sign up to set email alerts
|

Advanced glycation end-products and cathepsin cysteine protease in type 2 diabetic patients

Abstract: IntroductIon The most important consequence of hyperglycemia in type 2 diabetes is nonenzymatic glycation of various macromolecules, especially proteins, including those participating in the development of late diabetic complications (such as collagen, crystalline, and extracellular matrix components), and others (for example, enzymes). These issues have recently been extensively investigated. 1,2 The modifications in the structure of these macromolecules directly cause disturbances of their function, and, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…CtB has also been shown to be involved in diabetic nephropathy (Musante et al, 2015 ). Other reports demonstrate a reduction of CtB activity during polycystic kidney disease (Schaefer et al, 1996 ; Hartz and Wilson, 1997 ; Tao et al, 2005 ), puromycin induced nephrosis (Huang et al, 1999 ), and rat and human diabetic nephropathy (Shechter et al, 1994 ; Grzebyk et al, 2013 ; Peres et al, 2013 ). Conversely, CtB expression increased in unilateral ureteric obstruction mouse model, however, its inhibition led to no reduction in kidney fibrosis (Fox et al, 2016 ).…”
Section: Cathepsins In Chronic Kidney Disease (Ckd)mentioning
confidence: 94%
“…CtB has also been shown to be involved in diabetic nephropathy (Musante et al, 2015 ). Other reports demonstrate a reduction of CtB activity during polycystic kidney disease (Schaefer et al, 1996 ; Hartz and Wilson, 1997 ; Tao et al, 2005 ), puromycin induced nephrosis (Huang et al, 1999 ), and rat and human diabetic nephropathy (Shechter et al, 1994 ; Grzebyk et al, 2013 ; Peres et al, 2013 ). Conversely, CtB expression increased in unilateral ureteric obstruction mouse model, however, its inhibition led to no reduction in kidney fibrosis (Fox et al, 2016 ).…”
Section: Cathepsins In Chronic Kidney Disease (Ckd)mentioning
confidence: 94%
“…cellular matrix proteins, basement membrane proteins, and vessel-wall components, a process which alters their structure and function. Another important feature of AGE is their interaction with RAGE receptors, which are presented on the surface of a variety cells and which leads either to their endocytosis and degradation or to cellular activation and pro-oxidant, pro-inflammatory events [ 22 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…After 48 hours of dialysis in PBS with a one-time exchange of solution after 24 hours, the samples were frozen at −80°C for future analysis. The level of advanced glycation end products (AGE) was measured fluorimetry with the modified method described by Munch et al [ 22 , 23 ]. Briefly the characteristic fluorescence with excitation at 370 nm was measured at 440 nm with a spectrofluorimeter Perkin-Elmer LS50B.…”
Section: Methodsmentioning
confidence: 99%
“…AGEs also maintain vessel wall architecture by rendering ECM proteins less susceptible to protein degradation and by influencing the production of cathepsins and MMPs. 28 Grzebyk et al 29 found that circulating levels of AGEs were higher among patients with T2DM (p < 0.001) and that high AGE levels were associated with reduced plasma (p < 0.05) and neutrophil-derived (p < 0.01) levels of cathepsin B activity. Zhang et al 25,30 have also reported that AGEs can increase the production of MMP-9 in cultured macrophages but not in cultured AoSMCs.…”
Section: Ecm Glycation and Age Formationmentioning
confidence: 99%